2018
DOI: 10.7705/biomedica.v38i0.3417
|View full text |Cite
|
Sign up to set email alerts
|

SHTLV-I/II seroprevalence in blood donors of Hospital Pablo Tobón Uribe Blood Bank during the period 2014-2015

Abstract: Our findings were consistent with those found in similar studies in non-endemic areas of the country and with those from studies at international level reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A study that included all Colombian departments found an overall seropositivity of 0.3%, with most departments below 1% and Chocó being the only exception with 6.28% [239]. Similar studies from several blood banks from Medellin observed 0.06-0.176% positivity, mainly for HTLV-1 [243,244]. We also found two studies conducted on blood donors from Peru, Arequipa (0.9% HTLV-1 positive) and Abancay (3.4%, unknown subtype), and one in pregnant women from Lima (1.7% HTLV-1 positive) [253,254,256].…”
Section: Htlv Prevalence and Morbidity In Latin Americamentioning
confidence: 93%
“…A study that included all Colombian departments found an overall seropositivity of 0.3%, with most departments below 1% and Chocó being the only exception with 6.28% [239]. Similar studies from several blood banks from Medellin observed 0.06-0.176% positivity, mainly for HTLV-1 [243,244]. We also found two studies conducted on blood donors from Peru, Arequipa (0.9% HTLV-1 positive) and Abancay (3.4%, unknown subtype), and one in pregnant women from Lima (1.7% HTLV-1 positive) [253,254,256].…”
Section: Htlv Prevalence and Morbidity In Latin Americamentioning
confidence: 93%
“…In Peru, very few studies on HTLV-1 have been done in blood donors, showing a prevalence of around 0.9% [23]. Colombia shows a seroprevalence of HTLV-1/2 in the population of blood donors in Cali and Medellín of 0.24% and 0.176%-0.06%, respectively [24][25][26]. Also, a retrospective study analyzing screening and positivity for HTLV-1 and 2 data collected from 2001 to 2014 by Colombian blood banks, showed a cumulative reactivity of 0.30% [27].…”
Section: Resultsmentioning
confidence: 99%